Electrochemical corrosion kinetics of steel bars in pseudo-transparent concrete under different alkaline properties and chloride contamination levels - Bui, Huy Tang (2024)
Electrochemical kinetics of corroded steel bars is of importance in evaluating corrosion process and subsequent structural deterioration under different aggressive environments. This paper presents an experimental programme to investigate corrosion kinetics of steel bars in pseudo-transparent concrete subjected to different levels of chloride contamination and alkalinity in pore solution. The results show that corrosion current density increased with the rise of chloride content in simulated pore solution until Cl−/[OH−] ratio reached around 10. However, further chloride contamination with Cl−/OH−=12.5,15or20 tended to reduce current density. The phenomenon of decreasing corrosion rate and increasing corrosion potential when concrete was severely contaminated by chloride ions has not been widely reported in previous publications. An electrochemical mechanism was proposed based on the concepts of thermodynamics, anodic and cathodic polarisation kinetics to explain this extraordinary phenomenon, in which the decrease of corrosion current density when Cl−/[OH−] ratio increased from 10 to 20 was due to the rises of both anodic and cathodic Tafel slopes. On the other hand, a more neutralised pore solution in pseudo-transparent concrete induced a greater corrosion current density. When pH value was larger than 13, corrosion current density was negligible, while it substantially increased once pH value decreased to lower than 12.5.